2020
DOI: 10.1038/s41467-020-18396-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of human cardiac cells predicts protein kinase inhibitor-associated cardiotoxicity

Abstract: Kinase inhibitors (KIs) represent an important class of anti-cancer drugs. Although cardiotoxicity is a serious adverse event associated with several KIs, the reasons remain poorly understood, and its prediction remains challenging. We obtain transcriptional profiles of human heart-derived primary cardiomyocyte like cell lines treated with a panel of 26 FDA-approved KIs and classify their effects on subcellular pathways and processes. Individual cardiotoxicity patient reports for these KIs, obtained from the F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Despite being clinically efficacious, ponatinib has been associated with a high rate of cardiovascular adverse events, with a recent retrospective study finding 5% of patients with HF and more than 20% to experience an adverse cardiovascular event with ponatinib therapy [ 68 ]. Analysis of the FDA adverse event reporting system database has found ponatinib to carry the greatest risk of cardiotoxicity amongst all kinase inhibitors [ 69 ], with disproportionally high reporting of cardiac failure, ischaemic heart disease and hypertension compared to other anticancer therapies for CML [ 70 ].…”
Section: Metabolic Dysfunction Leading To Cardiotoxicity Of Specific Chemotherapiesmentioning
confidence: 99%
“…Despite being clinically efficacious, ponatinib has been associated with a high rate of cardiovascular adverse events, with a recent retrospective study finding 5% of patients with HF and more than 20% to experience an adverse cardiovascular event with ponatinib therapy [ 68 ]. Analysis of the FDA adverse event reporting system database has found ponatinib to carry the greatest risk of cardiotoxicity amongst all kinase inhibitors [ 69 ], with disproportionally high reporting of cardiac failure, ischaemic heart disease and hypertension compared to other anticancer therapies for CML [ 70 ].…”
Section: Metabolic Dysfunction Leading To Cardiotoxicity Of Specific Chemotherapiesmentioning
confidence: 99%
“…We investigated whether sGES alone can describe drug action on newly obtained transcriptomics data. We analyzed expression data from cardiomyocyte-like cell lines, generated by the Drug Toxicity Signature Generation (DToxS) LINCS Center, to identify perturbagen-specific cardiomyocyte response to specific drugs (40). We observed that certain over-and underrepresented protein folds distinguish kinase inhibitor response from anthracycline drugs (Fig.…”
Section: Train Algorithm Predictmentioning
confidence: 99%
“… 23 In a study of primary cardiomyocyte cell lines, exposure to tyrosine kinase inhibitors correlated with a p26‐gene expression signature and effectively predicted clinical cardiotoxicity. 24 Further, protein‐protein interaction analyses helped delineate individual kinases and transcription factors that may explain the signature and the associated cardiotoxicity.…”
Section: Preclinical Evaluation Of Anticancer Drug Candidatesmentioning
confidence: 99%